PERJUDIAN BILIAR DI MASYARAKAT DESA KIABU KECAMATAN SIANTAN SELATAN KABUPATEN KEPULAUAN ANAMBAS - Aneta; Siti Arieta; Sri Wahyuni (LPPM STISIP Persada Bunda, 2024)
The billiards game has become a deviant behavior for the community in Kiabu Village, the deviation occurs because of the gambling element in it. Billiards gambling that occurs among the Kiabu Village community is due to weak social control which causes unrest in the community. This research uses a qualitative approach, selecting informants using purposive sampling. Data collection techniques were carried out in three stages, namely by interview, observation, and documentation. Data analysis techniques use social control theory by Travis Hirschi. Data collection techniques through data reduction, data presentation, and conclusion drawing. The results of the study found that billiard games became gambling activities due to weak social control which should be carried out by families who have an important attachment and role in self-control to prevent family members from doing deviant behavior, education where boring learning methods make students bored to learn and feel bored in the educational environment, and village government where the lack of efforts from the village government in dealing with billiard gambling marks the weak relationship between the community and the village government. The conclusion of this study is that billiard gambling occurs due to weak external control, where the weak attachment between family, education, and village government to billiard gambling offenders that should exist in Kiabu Village.